Integrating Potential Land Use Conflict Into Ecological Security Pattern in Response to Land Use/Cover Changes at a County Scale in Yangtze River Delta, China - Peng, Wanting; Zhang, Zhiduo; He, Geng; Liu, Xiuyu; Wang, Wei; Cai, Yongli; López-Carr, David (Frontiers in Earth Science, 2022)
Identifying key ecological nodes/ corridors and priority restoration areas (KENPRA) is the key link to optimizing land use and ecological security patterns (ESP). However, few studies consider future land use/cover change (LUCC) and urban sprawl in identifying KENPRA for ESP maintenance. To optimize KENPRA , we took Quanjiao county, Anhui Province, China as a case study area, a typical unit for Chinese Land Spatial Planning and a suburb of Yangtze River Delta agglomeration challenging LUCC and ecological security pattern maintenance. A comprehensive framework for optimizing KENPRA has been established by integrating ESP and land use conflict (LUC), to adapt to land use change for corresponding urbanization processes. A CA-Markov model was used to predict future land use under different KENPRA-based scenarios in 2030.The results found that the total area of 4357.2 ha priority restoration areas and seventeen key ecological nodes was KENPRA, which were approximately 50% of them concentrated in intensive LUC areas. The result of the simulation model showed that KENPRA-based scenarios integrating LUC indicated less urban expansion and better effectiveness for maintaining ESP in 2030. The findings and proposed framework provide important new information and implications for planners and policymakers to understand and improve land planning/policy; results also can provide better understanding of the coupled human-nature system linking LUCC, ecosystem services and land and restoration planning.